Influence of light intensity, pre-harvest fasting, and storage time on biochemical components in serum and plasma of broilers - Clauber Polese; Lucas Wachholz; Cleison de Souza; Nilton Rohloff Junior; Guilherme Luis Silva Tesser; Rayanne Andrade Nunes; Cinthia Eyng; Jessica Dawn Starkey; Charles William Starkey; Jansller Luiz Genova; Ricardo Vianna Nunes (Revista Brasileira de Zootecnia)
ABSTRACT We determined the impacts of light intensity, fasting, and storage times on total protein (TP), albumin (ALB), globulin (Glb), uric acid (UA), creatinine (Cre), calcium (Ca), phosphorus (P), and alkaline phosphatase (ALP) in serum and plasma of broilers. At 42 days old, 140 broilers (3,123 ± 654 g) were assigned to two light intensities (5 or 20 lux m−2) and seven fasting times (0, 2, 4, 6, 8, 10, and 12 h). At 45 days old, blood collection was performed in all the broilers. Serum and plasma were stored in a freezer at −20 °C and analyzed on 0, 15, 30, 60, and 120 days. Higher concentrations of Cre and plasma Ca were observed at 20 lux, while the other components were observed at 5 lux. Serum ALB and Ca decreased with each hour of fasting, whereas ALP increased. Uric acid had the lowest concentration at 4 h and 51 min of fasting. Peak serum concentrations of Glb, TP, and Cre were at 6 h, 4 h and 30 min, and 5 h and 15 min of fasting, respectively. Plasma UA, Ca, and P had the lowest concentration at 3 h and 48 min, 5 h and 45 min, and 30 min of fasting, respectively, and a reduction in ALP. Serum UA, TP, and Glb concentrations increased with increasing storage time. Peak serum concentrations of Cre, P, and Ca were at 42, 119, and lowest at 82 days, respectively. Plasma Glb and ALP showed an increase with each storage day, while Cre decreased. Plasma UA and P showed the highest concentrations at 101 and 62 days, respectively. Plasma Ca showed a lower concentration at 50 days. The factors studied significantly influence key blood components in broilers. Higher light intensity increases Cre and Ca concentrations, while fasting reduces serum ALB and Ca, with variable peaks in other components. Storage boosts serum UA, TP, and Glb, with component-specific peaks and declines over time.